Characterizing the physical and mental health profile of children, adolescents and adults with autism spectrum disorder in Spain - Vidriales-Fernández, Ruth; Plaza-Sanz, Marta; Hernández-Layna, Cristina; Verde-Cagiao, María; Benito-Ruiz, Guillermo; Carvajal-Molina, Fernando (Frontiers in Psychiatry, 2023)
Introduction Autistic men and women are more likely to experience health issues than the general population, although the available epidemiological studies addressing co-occurrence conditions are limited. This is the first Spanish epidemiologic study addressing the health profile and poor-health exacerbating factors in individuals of all ages with autism spectrum disorder (ASD). Methods We analyzed 2,629 registries extracted from Autism Spain’s sociodemographic registry (November 2017–May 2020). A descriptive health data analysis was conducted to assess the prevalence of other conditions associated to ASD in the Spanish population. Nervous system disorders (12.9%), mental health diagnoses (17.8%), and other comorbidities (25.4%) were reported. Men-to-women ratio was 4:1. Results Women, elder individuals and those with intellectual disability (ID) were at an increased risk of health comorbidities and psychopharmacological exposure. Women were also more prone to severe intellectual and functional impairment. Nearly all individuals had difficulties in their adaptative functioning, especially those with ID (50% of the population). Almost half of the sample received psychopharmacological treatments starting from infancy and early childhood, mostly antipsychotics and anticonvulsants. Discussion This study represents an important first approach to the health status of autistic people in Spain and can contribute to the development of public policies and innovative health strategies.